Harvest timing and N application rate effects on switchgrass yield, nutrient cycling, and partitioning. (28th May 2017) - Seepaul, Ramdeo; Macoon, Bisoondat; Reddy, K. Raja; Evans, William B.
ABSTRACT: Harvest time (HT) and nutrient management may have an effect on switchgrass (Panicum virgatum L.) yield and nutrient cycling. Experimental objectives were to quantify HT and nitrogen (N) rate effects on dry matter yield (DMY), nutrient concentration, and N use. "Alamo" switchgrass was grown under four N rates (0, 40, 80, and 120 kg ha −1 ) with six monthly HT (May to October) in a randomized complete block design experiment with a split-plot arrangement. Yield increased cubically and quadratically with HT in Years 1 and 2. Aftermath yield decreased linearly with HT in both years. N rate increased yield in Year 2 only with no yield benefit at rates >40 kg N ha −1 . Nutrient concentration decreased from May to October, while its removal was determined by DMY. N use and recovery were greatest at 40 kg N ha −1 and declined with additional N inputs. Results indicate that harvesting post-frost-kill produced greater DMY with less nutrient concentration and removal.